Fairness in Educational Assessment and Measurement - Dorans, Neil J.; Cook, Linda L. (Taylor & Francis, 2016)
The importance of fairness, validity, and accessibility in assessment is greater than ever as testing expands to include more diverse populations, more complex purposes, and more sophisticated technologies. This book offers a detailed account of fairness in assessment, and illustrates the interplay between assessment and broader changes in education. In 16 chapters written by leading experts, this volume explores the philosophical, technical, and practical questions surrounding fair measurement. Fairness in Educational Assessment and Measurement addresses issues pertaining to the construction, administration, and scoring of tests, the comparison of performance across test takers, grade levels and tests, and the uses of educational test scores. Perfect for researchers and professionals in test development, design, and administration, Fairness in Educational Assessment and Measurement　presents a diverse array of perspectives on this topic of enduring interest.